Über einige Netze im dreidimensionalen euklidischen Raum - Padervinskas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Падервинскас. О некоторых сетях в трехмерном евклидовом пространствеV. Padervinskas. Apie kai kuriuos tinklus trimatėje euklidinėje erdvėje